Design and optimization of a spectrometer for high-resolution SD-OCT - Wang, Lulu (2020)
We report the design of a high-efficiency spectrometer for high-resolution spectral-domain optical coherence tomography (SD-OCT). The advantages of the proposed spectrometer are two-fold: first, we use a concave mirror instead of a camera lens (as typically used) as the focusing optics to both improve the transmission efficiency and eliminate chromatic aberrations; second, the efficiency of the proposed spectrometer is approximately 1.23 times that of a refractive optics-based spectrometer for an SD-OCT system, with comparable ranging depth and axial resolution. Both theoretical analyses and imaging experiments were conducted to characterize and validate the performance of the proposed spectrometer.